2015
DOI: 10.1152/ajpheart.00138.2015
|View full text |Cite
|
Sign up to set email alerts
|

Heat training increases exercise capacity in hot but not in temperate conditions: a mechanistic counter-balanced cross-over study

Abstract: The aim was to determine the mechanisms facilitating exercise performance in hot conditions following heat training. In a counter-balanced order, seven males (V̇o2max 61.2 ± 4.4 ml·min(-1)·kg(-1)) were assigned to either 10 days of 90-min exercise training in 18 or 38°C ambient temperature (30% relative humidity) applying a cross-over design. Participants were tested for V̇o2max and 30-min time trial performance in 18 (T18) and 38°C (T38) before and after training. Blood volume parameters, sweat output, cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
115
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 47 publications
13
115
2
Order By: Relevance
“…Although pronounced PV expansion was evident in both drinking conditions, there was no evidence of any change in VO 2max . This is in contrast to Lorenzo et al (2010), who demonstrated increased VO 2max concomitant with HA induced PV expansion, but is consistent with recent work showing no effect of HA induced PV expansion on VO 2max (Karlsen et al, 2015; Keiser et al, 2015). The reason for these equivocal findings is not entirely clear, although in Lorenzo et al (2010) the relative intensity of training sessions in the heat was higher than for a control group undertaking training under cool conditions and the possibility of an additional training stimulus cannot be excluded.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Although pronounced PV expansion was evident in both drinking conditions, there was no evidence of any change in VO 2max . This is in contrast to Lorenzo et al (2010), who demonstrated increased VO 2max concomitant with HA induced PV expansion, but is consistent with recent work showing no effect of HA induced PV expansion on VO 2max (Karlsen et al, 2015; Keiser et al, 2015). The reason for these equivocal findings is not entirely clear, although in Lorenzo et al (2010) the relative intensity of training sessions in the heat was higher than for a control group undertaking training under cool conditions and the possibility of an additional training stimulus cannot be excluded.…”
Section: Discussionsupporting
confidence: 89%
“…The reason for these equivocal findings is not entirely clear, although in Lorenzo et al (2010) the relative intensity of training sessions in the heat was higher than for a control group undertaking training under cool conditions and the possibility of an additional training stimulus cannot be excluded. Cardiovascular strain was matched between control and experimental groups in Keiser et al (2015), although it may have been higher in the experimental group of Karlsen et al (2015). Alternatively, while the effect of PV expansion on VO 2max appears unfavorable at the population level for trained individuals, there appears to be substantial inter-individual variation (Keiser et al, 2015), possibly due to individuality in the balance between increased cardiac output and the haemodilution effect on O 2 -carrying capacity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations